Male circumcision for HIV prevention: current evidence and implementation in sub-Saharan Africa - Wamai, Richard G (The International AIDS Society, 2011)
Heterosexual exposure accounts for most HIV transmission in sub-Saharan Africa, and this mode, as a proportion of new infections, is escalating globally. The scientific evidence accumulated over more than 20 years shows that among the strategies advocated during this period for HIV prevention, male circumcision is one of, if not, the most efficacious epidemiologically, as well as cost-wise. Despite this, and recommendation of the procedure by global policy makers, national implementation has been slow. Additionally, some are not convinced of the protective effect of male circumcision and there are also reports, unsupported by evidence, that non-sex-related drivers play a major role in HIV transmission in sub-Saharan Africa. Here, we provide a critical evaluation of the state of the current evidence for male circumcision in reducing HIV infection in light of established transmission drivers, provide an update on programmes now in place in this region, and explain why policies based on established scientific evidence should be prioritized. We conclude that the evidence supports the need to accelerate the implementation of medical male circumcision programmes for HIV prevention in generalized heterosexual epidemics, as well as in countering the growing heterosexual transmission in countries where HIV prevalence is presently low.